The 2003 Congress on Evolutionary Computation, 2003. CEC '03.
DOI: 10.1109/cec.2003.1299858
|View full text |Cite
|
Sign up to set email alerts
|

Constrained optimization based on a multiobjective evolutionary algorithm

Abstract: -A criticism of Evolutionary Algorithms (EAs) might be the lack of efficient and robust generic methods to handle constraints. The most widespread approach for constrained search problems is to use penalty methods. EAs have received increased interest during the last decade due to the ease of handling multiple objectives., A constrained Optimization problem or a n unconstrained multiobjective problem may in principle be two different ways to pose the same underlying I problem. In this paper an alternative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…From this study, the suitable range for B values was found to be from 0.01 (1%) to 0.2 (20%). It has to be noted that some of the best solutions found were even better than the optimal values, which is due to the approximation of the equality constraints into inequality constraints using (1).…”
Section: Experimental Results and Discus-sionsmentioning
confidence: 99%
See 4 more Smart Citations
“…From this study, the suitable range for B values was found to be from 0.01 (1%) to 0.2 (20%). It has to be noted that some of the best solutions found were even better than the optimal values, which is due to the approximation of the equality constraints into inequality constraints using (1).…”
Section: Experimental Results and Discus-sionsmentioning
confidence: 99%
“…The ranking methodology used here is fast and direct as the information from the constraint violation are represented by the sum of squares value and the number of constraints violated. This is in contrast to the time consuming pareto ranking which needs to take into account the values of each constraint function separately (e.g., in [1] and [8]). The biggest contribution from this work is the idea of using ranking to convert the information from the objective function and constraint violation into values which are in the same order of magnitude, such that direct summation of the ranking terms can then be used to integrate all of the information into one term.…”
Section: Experimental Results and Discus-sionsmentioning
confidence: 99%
See 3 more Smart Citations